Students’ Anxiety in Undergraduate Thesis Writing - Prasetyaningrum, Ari; Ayu Suraya, St; Dwi Maulani, Astrid; Wati, Laila (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2026)
Undergraduate thesis is the final task that must be submitted by students of the English Study Program at Hamzanwadi University as proof of their achievement in conducting scientific research. However, the process of writing an undergraduate thesis often causes anxiety since the students come from an English as a Foreign Language (EFL) context. This study aimed to analyze the level and types of anxiety. A descriptive quantitative approach was used in this study. The study involved 20 students as participants. The researchers distributed questionnaires to identify the students’ anxiety level and types of anxiety during the process of undergraduate thesis writing. According to the findings from the questionnaires, the students experienced a severe level of anxiety, with the dominant types being somatic anxiety, followed by cognitive anxiety and avoidance behaviour. Therefore, it is necessary to provide strategies to improve students’ competence and self-confidence so that they can produce a qualified final task.